UPAYA PENCEGAHAN PERILAKU BULLYING MELALUI SOSIALISASI PENDIDIKAN KARAKTER DI SDN 2 PEUNARON KABUPATEN ACEH TIMUR - Munadiati, Munadiati; Yulfita, Uti; Rangkuti, Widatul Zanna; Sakila, Arifa Dara; Rahmah, Elsa Auliana; Rahimah, Dewi; Syifa, Hafni Dwi; Hafizhah, Zuhrah; Sabila, Amalia Dwi; Amanda, Risa Yuni; Silvia, Riska; Pratiwi, Melani Dea; Lestari, Ayu; Riski, Muhammad Anjas (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2025)
Bullying remains a critical issue in elementary schools, including at SDN 2 Peunaron, East Aceh Regency, as it significantly affects children’s social and emotional development. A safe, supportive, and conducive learning environment is essential to ensure students’ holistic growth. This community engagement program was designed to raise students’ awareness of the harmful effects of bullying while simultaneously fostering core character values such as empathy, responsibility, and mutual respect. The program applied an interactive socialization approach through lectures, group discussions, and educational games that encouraged active student participation. The outcomes indicate that students demonstrated an improved understanding of various forms of bullying, recognized their negative consequences, and showed positive behavioral changes in daily interactions. In addition, teachers gained deeper insights into effective strategies for preventing and addressing bullying within the classroom. These findings highlight that character education-based socialization is an effective preventive strategy to reduce bullying and strengthen character formation among elementary school students.